2001
DOI: 10.1046/j.1365-2044.2001.01985.x
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro performance of carbon dioxide absorbents with and without strong alkali

Abstract: We report the in vitro longevity of a conventional soda lime carbon dioxide absorbent and an absorbent free from strong alkali (Amsorb™). Although the times taken to breakthrough of carbon dioxide (> 0.5%) within an in vitro low flow breathing systern were shorter with the alkali‐free absorbent, we found that the size and shape of the absorbent container was the major factor in determining the efficiency of the carbon dioxide absorbents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…In the latter study, however, values were reported after cumulative discontinuous clinical use, whereas our values resulted from a continuous use. For Amsorb ® Plus the utilisation time in our study was 17.1 h and for DrägerSorb ® Free it was 20.6 h. This contrasts with the reported time of up to 6 h to reach 0.5 kPa CO 2 using 1000 g Amsorb ® in vitro in a Julian ® cannister [12]. The longer utilisation time noticed by us with DrägerSorb ® Free would be a definite practical clinical advantage.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In the latter study, however, values were reported after cumulative discontinuous clinical use, whereas our values resulted from a continuous use. For Amsorb ® Plus the utilisation time in our study was 17.1 h and for DrägerSorb ® Free it was 20.6 h. This contrasts with the reported time of up to 6 h to reach 0.5 kPa CO 2 using 1000 g Amsorb ® in vitro in a Julian ® cannister [12]. The longer utilisation time noticed by us with DrägerSorb ® Free would be a definite practical clinical advantage.…”
Section: Discussioncontrasting
confidence: 83%
“…It has been reported that the CO 2 absorption capacity of Amsorb ® concentrations is 10–15% less than that of soda lime [11,12] and even up to 50% less in another study [13]. During an in vivo study with low‐flow conditions, the CO 2 absorption capacity was only half that of soda lime and it was somewhat less using a compact 750‐ml ADU ventilator cannister than using a 1360 ml Aestiva 3000 ® cannister (Datex Ohmeda, Helsinki, Finland) [14].…”
Section: Discussionmentioning
confidence: 99%
“…The most likely reason is because different canister designs were used in each period: 600g in the manual phase and 800g in the Et control phase. CO 2 absorbents in larger canisters have consistently been shown to have higher absorptive capacities 25,26 . This is because an absorbent is at its most efficient when a patient's tidal volume is equal to the void space (the air between the granules) within the canister 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The monovalent hydroxides are more reactive than the divalent Ca(OH) 2 . 10 Where crystals have been allowed to dry out, such as leaving the gas flowing through the canister overnight, these highly reactive monovalent hydroxides can also produce significant amounts of carbon monoxide and even formaldehyde, 11,12 which are toxic to subsequent patients. As well as absorbing CO 2 , the absorbents also tend to absorb volatile anaesthetic agents themselves; 13 this is generally acceptable, though wasteful, but certain agents can produce neurological toxins, for example, trichloroethylene (no longer available) reacting with soda lime-produced dichloroacetylene gas (phosgene).…”
Section: Anaesthetic Circle Systemsmentioning
confidence: 99%